2022
DOI: 10.3390/cancers14225591
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging in Major Hepatectomies: Preliminary Results from the Ex-Machyna Trial

Abstract: Ischemia-reperfusion injury during major hepatic resections is associated with high rates of post-operative complications and liver failure. Real-time intra-operative detection of liver dysfunction could provide great insight into clinical outcomes. In the present study, we demonstrate the intra-operative application of a novel optical technology, hyperspectral imaging (HSI), to predict short-term post-operative outcomes after major hepatectomy. We considered fifteen consecutive patients undergoing major hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Potential surgical applications of the hyperspectral camera’s indexes have already been investigated [ 15 , 16 , 17 ], but another valuable application of our method could be the intraoperative estimation of remnant liver congestion. Recently, it has been reported that remnant liver ischemia should be carefully considered in human oncological settings because of a significantly increased risk of morbidity, recurrence, and mortality [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential surgical applications of the hyperspectral camera’s indexes have already been investigated [ 15 , 16 , 17 ], but another valuable application of our method could be the intraoperative estimation of remnant liver congestion. Recently, it has been reported that remnant liver ischemia should be carefully considered in human oncological settings because of a significantly increased risk of morbidity, recurrence, and mortality [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSI is a non-invasive, contrast-free tool recently applied in several medical and basic research fields [ 5 , 6 ], like other new emerging technologies [ 7 , 8 ]. Several innovative approaches are under investigation that exploit the capability of HSI to “see beyond” the visible range, such as intraoperative tissue recognition [ 9 ], therapy guidance, and monitoring [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imaging technology (HIT) is the most representative, which has the advantage of "image and spectrum in one", with high resolution, continuous channels, more wavebands, and more vital discriminatory ability [13]. HIT originated in remote sensing and has since been widely used in many fields such as feature identification [14,15], environmental monitoring [16,17], agricultural quality inspection [18,19], medical diagnosis [20,21], and criminal forensic investigation [22,23].…”
Section: Introductionmentioning
confidence: 99%